Endocarditis and the impact of intravenous drug use: a cohort study. Issue 10 (3rd October 2021) - Lawrence, Christopher H. D.; Cheaveau, James; Kavourides, Michalis; Chadwick, David; McCarron, Brendan
Abstract: Objectives: This cohort study is a comparison of infective endocarditis in intravenous drug users (IDUs) and non-IDUs within a single tertiary centre. We aim to quantify and describe the factors that influence prognosis and microbiological characteristics. Method: All consecutive admissions to a tertiary referral hospital in the north of England with a diagnosis of endocarditis from April 2013 to January 2020 were identified. Outcomes were all-cause mortality at 30 days, 12 months and 3 years, length of stay and progression to surgery. Results: A total of 303 cases were identified via clinical coding of which 287 cases of endocarditis were confirmed. First episode endocarditis was then confirmed in 263 episodes, 44 in IDUs and 219 in non-IDUs. Methicillin sensitive Staphylococcus aureus (MSSA) was the most common organism seen overall, significantly more so in IDU than non-IDU cases (29/44 [65.9%] vs. 51/219 [23.3%], p < .001). Overall progression to valve surgery was similar between the two groups (92/219 [42.0%] vs. 19/44[43.2%], p = .886). In IDUs 30-d survival was 93% (80–98) and 3-year survival 47% (30–63%). In non-IDU 30-d survival was 88% (83–92%) and 60% (53–67%) at 3 years. Of the 19 IDUs who underwent valve surgery 7 (37%) survived to study completion without reinfection and 8 (42%) died following recurrent endocarditis. Conclusions: We demonstrate that prognosis in IDUs is worse than previously described, particularly in those undergoing valve surgery. This is despite comparable receipt of inpatient treatment to non-IDUs as demonstrated by equal length of stay and rates of surgery. Clinicians should consider the role of addictions services on discharge to break the cycle of reinfection.